Non-equilibrium dynamics of Bose-Einstein condensates - Welch, Nathan (2015)
In the following work we investigate the dynamics of Bose-Einstein condensates(BECs) under the influence of time-dependent potentials. The response of such a sensitive system to external perturbations is a matter of increasing interest. This is because of the enormous growth in understanding the physics and emerging applications of BECs in many areas of physics such as sensing, microscopy and quantum information.